Leveraging Data Analytics and Customer Insights for Market Positioning in Ghana - Aboagye, Felix (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to examine leveraging data analytics and customer insights for market positioning in Ghana Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Leveraging data analytics and customer insights for market positioning in Ghana offers a transformative advantage for organizations seeking to strengthen their competitive edge in a dynamic and evolving market. By harnessing the power of data analytics, companies can gain deep, actionable insights into consumer behaviors, preferences, and trends, enabling them to tailor their products, services, and marketing strategies to meet the specific needs of the Ghanaian market. Unique Contribution to Theory, Practice and Policy: Agency Theory, Resource Dependence Theory & Stewardship Theory may be used to anchor future studies on leveraging data analytics and customer insights for market positioning in Ghana. Organizations should invest in advanced analytics tools and technologies to enhance their data processing and interpretation capabilities. This will enable them to generate deeper customer insights and improve market positioning. Firms should provide continuous training and development for employees in data analytics to ensure they have the necessary skills to leverage customer insights effectively. This can enhance the overall data literacy within the organization. Policymakers should develop and enforce robust data governance frameworks that ensure data privacy and security. This will help in addressing ethical concerns and building consumer trust in data analytics practices. Governments and industry bodies should promote data literacy and education programs to equip the workforce with the necessary skills to handle and analyze data effectively. This can enhance the overall competitiveness of businesses.